Предмет: Алгебра,
автор: olgaslizo
упростите выражение а(а-2)(а-2)-(а-3)(а^2+3а+9)
Ответы
Автор ответа:
8
(a-3)(a²+3a+9)=a³-b³
a(a-2)(a-2)-(a-3)(a²+3a+9) = a(a²-4a+4)-(a³-b³) =
=a³-4a²+4a-a³+b³ = b³-4a²+4a = b³-4a(a-1)
a(a-2)(a-2)-(a-3)(a²+3a+9) = a(a²-4a+4)-(a³-b³) =
=a³-4a²+4a-a³+b³ = b³-4a²+4a = b³-4a(a-1)
Похожие вопросы
Предмет: Другие предметы,
автор: fruktikfruktik065
Предмет: Математика,
автор: fbv7dq24s2
Предмет: Русский язык,
автор: pnkponika
Предмет: Математика,
автор: айбатик3
Предмет: Алгебра,
автор: Grischa228